Employers' Perception Toward Universiti Sains Islam Malaysia (USIM) Graduates 2003-2013 - Mahazan Abdul Mutalib @ Talib; Musa, A.H.; Mohd. Yahya, M.A.; Azman, A.R; Awangku Abdul Rahman, A.Y; Mohd. Rozaini, A.R (Universiti Sains Islam Malaysia, 2024)
This study investigated the perception of employers toward USIM graduates from 2003 until 2013. Graduate skills investigated for this research are communication skills, thinking and problem-solving skills, teamwork, information management and ICT, entrepreneurship and work planning, ethics and professionalism, leadership skills, and finally religious orientation in organisation. Two categories of background data collected from the graduates are the faculty at USIM which they had enrolled, and the respondents career sector. The purpose of this study is to provide a descriptive analysis on the perception of employers toward USIM graduates from 2003 until 2013. This study applied the survey technique on 350 randomly selected graduates around Malaysia. In the first phase of this research, from 120 samples, this research was able to gather information from 70 employers. Results of the descriptive analysis show that USIM graduates were perceived to be good in religious orientation, information management and ICT, and ethic and professionalism, by the employers. Data from the sector of employment shows that most of the respondents were from the education sector.